Importancia del Pseudo-Apolodoro para el lector de la Alcestis de Eurípides - López Férez, Juan Antonio (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2015)
This paper, based on the reading and analysis of Euripidean Alcestis, wants to stress the importance of the tragic to understand the text of Pseudo-Apollodorus and, at the same time, to indicate the interest of the last one to complete and understand certain aspects of the mentioned play of Euripides